Psychologiczna charakterystyka perfekcjonizmu u młodzieży - Świerczyńska, Justyna; Pawłowska, Beata; Chojnowska- Ćwiąkała, Izabela; Troczyńska, Beata (Wydawnictwo Naukowe EDUsfera. Ewa Jurczyk-Romanowska, 2021)
The aim of the work was to compare the intensity of perfectionism in the study subjects, considering their division by sex, place of residence and family structure.
Keywords: perfectionism; sex; youth; demographic factors